EVALUATION OF WOUND HEALING OUTCOMES AFTER BELOW-THE-KNEE ENDOVASCULAR INTERVENTION IN PATIENTS WITH CHRONIC LIMB-THREATENING ISCHEMIA (Vietnam Journal of Community Medicine, 2026)
Objective: To describe lesion characteristics and evaluate wound healing outcomes after below-the-knee endovascular intervention in patients with chronic limb-threatening ischemia.Methods: This retrospective descriptive case-series included 71 patients with chronic limb-threatening ischemia and ischemic ulcers who underwent below-the-knee endovascular intervention at Thong Nhat Hospital between January 2024 and December 2024.Results: The average age of the patients was 75.6 ± 9.8 years, with a predominance of males (76.1%); diabetes mellitus was present in 53.5% of patients. The anterior tibial artery was the most frequently affected vessel, accounting for 39.4% of lesions in the small-ulcer group and 22.5% in the large-ulcer group. Patients with large ulcers had significantly higher rates of occlusion of all three below-the-knee arteries (12.7%) and pedal arch occlusion (26.8%) compared with those with small ulcers (p < 0.05). At 12-month follow-up, wound healing rates were 22.5% in patients with three-vessel below-the-knee revascularization, 29.6% in those with two-vessel revascularization, and 11.3% in patients with single-vessel revascularization.Conclusion: Below-the-knee endovascular intervention is effective in promoting wound healing in patients with chronic limb-threatening ischemia. A multivessel revascularization strategy combined with restoration of the pedal arch is a key determinant of limb salvage.
Keywords: Chronic limb-threatening ischemia (CLTI), endovascular intervention, below-the-knee lesions, wound healing.